Callus culture and regeneration from root tip of garlic (Allium sativum L.) - Lawande, Anil Khar, A Asha Devi, K E (Journal of Spices and Aromatic Crops, 2005)
Callus induction and subsequent plant regeneration was studied in acommercial Indian cultivar of garlic, cV. G-41 (short-day type). 2,4-dicholorophenoxyacetic acid at lower concentration (0.25 mg 1-1) and picloram at higher concentration 1.0 mg 1") were suitable for efficient callus formation from the root tips. Callus was obtained only from the apical portions of root-tips treated with 2,4-dicholorophenoxyacetic acid whereas picloram led to callus fo rmation throughout the root segment except the non apical (subjacent) portion. Callus obtained from induction medium containing both auxins and cytokinins responded well to regeneration. The average shoot regeneration frequency ranged from 16.7% to 50.0%. The best combination for callus culture and regeneration was callus formation in root tip medium 2 (CRT 2) (2,4-d icholorophenoxyacetic acid 0.25 mg 1" + 6-benzylaminopurine 1.0 mg I'') induction medium followed by garlic regeneration medium 3 (GR 3) (ki netin 1.0 mg 1") as the regeneration medium. In other regeneration media, profuse root formation and appearance of dark green callus was also observed.